2018
DOI: 10.1115/1.4040128
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis for Influence of Parametric Uncertainty on the Stability of Rotor System With Active Magnetic Bearing Using Feedback Linearization

Abstract: Active magnetic bearing (AMB) is the device to support and control rotating shaft. Feedback linearization is one of the methods to compensate the system nonlinearity, and it is often used in the control of AMB. Some parameters in the electromagnetic force model have often been ignored or their parametric uncertainty from the nominal values has been calibrated; however, their influence on the stability has not been investigated. In this paper, the influence of the parametric uncertainty in the electromagnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, the variabilities of the natural characteristics, critical dynamic responses and any other important findings should be also experimentally verified and it is mandatory to demonstrate the various techniques proposed are reliable. Some works present good results that are validated experimentally, for example, the analyses of measurement uncertainty [88], the parameter identification of faults or bearings [166,256], characterizing the influence of uncertainty in rotor balancing [44,175], control problems [225] and validations of nonlinear FRFs [298]. However, the number of experimental studies on this topic is limited and it is far from sufficient because standard strategies and mature experiment methods are still missing.…”
Section: Discussion and Outlooksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the variabilities of the natural characteristics, critical dynamic responses and any other important findings should be also experimentally verified and it is mandatory to demonstrate the various techniques proposed are reliable. Some works present good results that are validated experimentally, for example, the analyses of measurement uncertainty [88], the parameter identification of faults or bearings [166,256], characterizing the influence of uncertainty in rotor balancing [44,175], control problems [225] and validations of nonlinear FRFs [298]. However, the number of experimental studies on this topic is limited and it is far from sufficient because standard strategies and mature experiment methods are still missing.…”
Section: Discussion and Outlooksmentioning
confidence: 99%
“…The research on nonlinear rotordynamics under uncertainty is more difficult than the linear studies since there are interactions between nonlinearities and uncertainties. Some papers investigated the nonlinear dynamics of the rotor-AMBs systems [64,225,226] and cracked rotor systems [47,75,76,115,227,228]. Nonlinear analysis techniques, such as the alternating frequency/time technique (HB-AFT), orthogonal polynomial approximation and linearization, are used to deal with nonlinearities.…”
Section: Natural Characteristics and Unbalanced Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the AMB based rotor exhibit amplitude hopping and multi frequency vibration under the action of the nonlinear electromagnetic force, and the nonlinear dynamic response of the system could be effectively affected by changing the magnitude of the external excitation. Literature [23] studied the influence of the uncertainty of electromagnetic force parameters on the stability of the AMB control system, and proved that when the electromagnetic force parameters contained the uncertainty of parameters, additional equilibrium points would appear in the case of feedback linearization, and these additional points would seriously affect the stability of the system, causing the system to diverge due to initial conditions or disturbances. The above results have a more thorough explanation of the nonlinear electromagnetic force its influence, but there is no internal relationship between it and the low frequency vibration of the rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Methods like sensitivity analysis [24], numerical simulation [25], and feedback linearization etc. [26] have been applied by scholars in studying the influence analysis of dynamic system parameters. In terms of parameter optimization, multi-factor design optimization has become the major research direction.…”
Section: Introductionmentioning
confidence: 99%